Association between triglyceride-glucose index and acute kidney injury in patients with acute myocardial infarkt based on Medical Information Mart for Intensive Care database: A cross-sectional study: Triglyceride-Glucose Index and Acute Kidney Injury in Myocardial Infarction - Jin, Zihan; Xiao, Lu; Xu, Xinyi; Miao, Changhong; Liu, Yi (Journal of Medical Biochemistry, 2023)
Background: The relationship between triglyceride glucose (TyG) index and the incidence of acute kidney injury (AKI) in patients with acute myocardial infarction (AMI) is unclear. This study aims to explore the relationship between the two.Methods: Participants were enrolled from Medical Information Mart for Intensive Care IV (MIMICIV) and grouping of subjects based on the quartile interval of the TyG index. With the presence of AKI as the main outcome, a logistic regression model was constructed. The correlation of the TyG index with the results obtained was examined by using a restricted cubic spline (RCS) model.Results: Among the 1,101 AMI participants, 64.7% were male patients and the overall incidence rate of AKI was 37.1%. The results of multivariate Logistic regression analysis (LRA) revealed independent correlation of the TyG index with increased AKI risk (odds ratio (OR) = 2.23; confidence interval (CI) = 1.59 to 3.17; P < 0.001). Q4 (9.5-12.208) in the TyG index quartile was independently correlated with increased AKI risk (OR = 2.99, 95% CI = 1.64 to 5.46, P < 0.001). The RCS model showed that the AKI risk increased linearly as the TyG index increased (P=0.313).Conclusion: In patients with AMI, the incidence of TyG and AKI is closely related. Nevertheless, further studies are needed to verify the finding.